Data synchronization between mobile devices and server-side databases: A systematic literature review - Imam, A.A. (Asian Research Publishing Network, 2015)
It is progressively important for mobile device databases to achieve additional coordination of diverse computerized operations. To do so, many research works have been conducted to attain more companionable solutions that can be used to synchronize data between the mobile device and the server side databases. The objective of this study is to survey the state of the art in various aspects of mobile devices with respect to data sharing and synchronization between mobile device databases and server-side databases as opposed to the server-to-server synchronizations. To achieve this feat, 5 different electronic databases were used to identify primary studies using the relevant keywords and search terms related to mobile data synchronization classified under journals, conferences, symposiums and book chapters. The study produced interesting results in different areas such as data synchronization, data processing, vendor dependency, data inconsistency and conflicts resolutions where 19 primary studies were selected from the search processes. In our conclusion, mobile data synchronization has been significantly discussed in the domain of databases. In general however, it was discovered that, existing synchronization solutions suffer from a number of limitations such as lack of consistency among data, resolving conflicts, data processing responsibility, vendor dependency, data type, bandwidth utilization and network fluctuation during data transmission. Also the applicability of the existing solutions has not been reported yet. Â© 2005 - 2015 JATIT & LLS. All rights reserved.